PENGARUH STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) BERBANTUAN LKS TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SEMESTER II SMAN 2 PARIAMAN - Yani Kurnia Sapta Rika (Universitas Negeri Padang, 2013)
In this research, background of the problems are students’ low in scores and lack of motivation in increasing their thinking ability because teaching learning process is more dominated by the teacher. An inappropriate strategy in teaching learning process makes students become lack of interaction that leads them to find out physics concepts during teaching learning process. This study aims to investigate Effect of Strategi Pembelajaran Peningkatan kemampuan Berpikir (SPPKB) by using LKS toward Physics’ Learning Outcomes.Type of this research is Quasi-Experimental Research. Randomized Only Control Group Design is used in this research. The populations of the research are all tenth grade students in SMAN 2 Pariaman registered in the academic year 2013/2014. Cluster random sampling technique is used to take the sample. The sample of the research is X1 class consisted of 31 students and X2 class consisted of 33 students. Variables consisted of the independent variables with the application of SPPKB by using LKS. Dependent variable is the students’ learning outcomes, and control variables are the teacher, materials and the allocated time that is given for both of them are similar. Procedure of the research consists of preparation, implementation, and conclusion. Technique of data collection is through a written test for the cognitive, affective aspect and observation for psychomotor aspect. Technique of data analysis is by using the hypothesis test of equality of two average tests by using t-Test at real level 0.05 for the cognitive, affective, and psychomotor aspect. The hypotheses of the test is about the equality of two test average two-party testing criteria; accept Ho if -t (1-1/2 α) <t <t (1-1/2 α). The score of T tabel for each aspect is 2.00. t hitung for cognitive aspect is 4.06, then t hitung > t table (4.06> 2.00); t hitung for affective aspect is 2.29 so that t hitung> t table (2.29> 2.00); t hitung for psychomotor aspect is -2.54 then t hitung < t table (-2.54 <2,00). The results of these three aspects are in the rejection area of Ho, so that there is a significant difference in learning outcomes between the experimental class and the control class. So, it happens because of the effect of SPPKB by using LKS on temperature and heat lesson in learning outcomes of students in physics. So,it can conclude that hypothesis of “that effect of SPPKB by using LKS on the temperature ans heat lesson in study physics in class X SMAN 2 Pariaman” can be accept at the real level 0,05. Keywords: Learning Strategy, SPPKB, Worksheet, Learning Outcome